2005
DOI: 10.1007/s10533-004-0368-7
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in soil carbon and δ13C in forests and pastures of northeastern Costa Rica

Abstract: Recent studies suggest that the direction and magnitude of changes in soil organic carbon (soil C) pools following forest-to-pasture conversion in the tropics are dependent upon initial soil conditions and local factors (e.g. pre-conversion soil C content, soil texture, vegetation productivity, and management practices). The goal of this study was to understand how landscape-scale variation in soil-forming factors influenced the response of soil C pools to forest clearing and pasture establishment in northeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 39 publications
4
56
1
Order By: Relevance
“…If possible, turnover times were calculated after equation 1 and 2. Data from this study (black symbols) and from : Veldkamp 1994;Townsend et al 1995;Osher et al 2003;Rhoades et al 2000;Powers and Veldkamp 2005 (volcanic ash soils); Desjardins et al 1994Desjardins et al , 2004Feigl et al 1995;Koutika et al 1997;Powers and Veldkamp 2005;Schwendenmann and Pendall 2006 (open symbols). Note, high turnover times in young pastures are probably due to considerable C 3 (herbs and bushes) input Appendix A Values are given as mean and SD (n = 4) nd, not determined Table A2 Total dry matter yield, soil C storage (g kg -1 soil ), soil C concentration (g kg -1 sandfree aggregates), C/N, and d …”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…If possible, turnover times were calculated after equation 1 and 2. Data from this study (black symbols) and from : Veldkamp 1994;Townsend et al 1995;Osher et al 2003;Rhoades et al 2000;Powers and Veldkamp 2005 (volcanic ash soils); Desjardins et al 1994Desjardins et al , 2004Feigl et al 1995;Koutika et al 1997;Powers and Veldkamp 2005;Schwendenmann and Pendall 2006 (open symbols). Note, high turnover times in young pastures are probably due to considerable C 3 (herbs and bushes) input Appendix A Values are given as mean and SD (n = 4) nd, not determined Table A2 Total dry matter yield, soil C storage (g kg -1 soil ), soil C concentration (g kg -1 sandfree aggregates), C/N, and d …”
Section: Discussionmentioning
confidence: 84%
“…A study in Brazil also reported a more rapid increase of pasture-derived carbon in a coarse textured soil than in a clay soil (Desjardins et al 2004). However, other field studies do not support this observation (Desjardins et al 1994(Desjardins et al , 2004Feigl et al 1995;Koutika et al 1997;Powers and Veldkamp 2005;Schwendenman and Pendall 2006). Texture effects are often masked by other effects like clay mineralogy, land use history, or management (Saggar et al 1996;de Koning et al 2003;Powers and Veldkamp 2005).…”
Section: Sitementioning
confidence: 93%
See 2 more Smart Citations
“…When including other soil types, our disturbed forest had SCS values (61.4 Mg ha −1 ) higher than most reported SCS values, with the exception of SCS values reported for a region in Mato Grosso (65.3 Mg ha −1 ) and another in Rondônia (62 Mg ha −1 ; Maia et al, 2009). The SCS can be influenced by soil type, texture, and mineral composition (Powers and Veldkamp, 2005;López-Ulloa et al, 2005;Neumann-Cosel et al, 2011). Indeed, the different SCS rates from different soil types are related to important factors such as geology, climate, and soil formation (Adams et al, 1990;Batjes, 1996).…”
Section: Estimates Of Soil Carbon Stocksmentioning
confidence: 99%